2013
DOI: 10.1007/s11033-013-2842-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of HSL gene E1-c.276C>T and E8-c.51C>T mutation with economical traits of Chinese Simmental cattle

Abstract: Hormone-sensitive lipase (HSL) is responsible for the decomposition of triglycerides in adipose tissue to release free fatty acids, and it is a key rate-limiting enzyme in the regulation of adipose tissue deposition and decomposition. The objective of this study was to evaluate the association between novel SNPs in the coding region of bovine HSL gene and carcass and meat quality traits of Chinese Simmental-cross steers. Two novel SNPs were genotyped and the 47 traits of carcass and meat quality traits were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…1). The present findings showed that the LIPE gene of pig, cattle, water buffalo, camel, goat and sheep is polymorphic in nature and earlier studies have associated polymorphism of the LIPE gene with superior milk yield and milk fat contents, carcass characteristics including muscle thin, fat thickness of back, intra-muscular fat in different species etc [8,9,10,19]. More so, the amino acid substitution revealed both neutral and deleterious variants of LIPE gene in all the six studied species.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…1). The present findings showed that the LIPE gene of pig, cattle, water buffalo, camel, goat and sheep is polymorphic in nature and earlier studies have associated polymorphism of the LIPE gene with superior milk yield and milk fat contents, carcass characteristics including muscle thin, fat thickness of back, intra-muscular fat in different species etc [8,9,10,19]. More so, the amino acid substitution revealed both neutral and deleterious variants of LIPE gene in all the six studied species.…”
Section: Discussionsupporting
confidence: 63%
“…The amino acid substitution that returned neutral indicates that the substitution did not have any damaging effect on the structure and function of the protein while those deleterious amino acid substitution predictions were harmful and could cause an alteration or impairment of protein functions which may lead to impair energy balance, low levels of circulating fatty acid, adipocyte hypertrophy, lipid-filled macrophages and an increase in basal lipolysis particularly in lactating animals [20,21,22]. This is because the synthesis of milk components involves the mobilization of lipid depots to satisfy the large energy demands of the mammary gland [8]. The phylogenetic tree obtained based on the nucleotide sequences of the studied species suggests that goat was more related with water buffalo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the differentially methylated genes identified in the present study between Wagyu and Chinese Red Steppes are also found to be differentially methylated in genes related to lipid metabolism and fatty acid metabolism, such as fatty acid synthase ( FASN ) which is shown to be related to fatty acid composition in a genome-wide association study of Japanese black cattle [43], and carnitine palmitoyltransferase 1A ( CPT1A ), fatty acid desaturase 1 ( FADS1 ) and acyl-CoA synthetase long-chain family member 1 ( ACSL1 ) genes which are well-known genes in the pathways of fatty acid metabolism and fatty acid degradation. In addition, other genes known to affect meat quality traits of cattle are also related to the lipid metabolism and fatty acid metabolism ( insulin like growth factor 2 ( IGF2 ), leptin ( OB ), lipase hormone sensitive ( HSL ), diacylglycerol O-acyltransferase 1 ( DGAT1 ) and fatty acid binding protein 3 ( FABP3 )) [4449]. We believed that the methylation of these genes might partially contribute to the significant variance in meat quality traits between Japanese black cattle and Chinese Red Steppes.…”
Section: Discussionmentioning
confidence: 99%
“…, 2005 ). Recently, two SNPs have been successfully associated with carcass and meat quality traits in Chinese Simmental-cross steers ( Fang et al . , 2013 ).…”
Section: Introductionmentioning
confidence: 99%